Melancholy and the archive : trauma, history and memory in the contemporary novel - Boulter, Jonathan, 1967- (Continuum literary studies., 2011)
Melancholy and the Archive examines how trauma, history and memory are represented in key works of major contemporary writers (David Mitchell, Paul Auster, Haruki Murakami, Jose Saramago). The book explores how these authors construct crucial relationships between sites of memory the archive becomes a central trope here and the self that has been subjected to various traumas, various losses. The archive be it a bureaucratic office (Saramago), an underground bunker (Auster), a geographical space or landscape (Mitchell) or even a hole (Murakami) becomes the means by which the self attempts to pr.